The Aramaic books of Enoch and related literature from Qumran proceedings of the international online conference, organized by the Center for the Study of Second Temple Judaism of the John Paul II Catholic University of Lublin, in cooperation with Enoch Seminar, 20-22 october 2020 - Drawnel, Henryk (Leiden Boston Brill, 2024)
"This volume contains studies that explore the content and meaning of the Qumran manuscripts of the Aramaic Books of Enoch, the Book of Giants, and related literature. The essays shed new light on the lexicon, orthography and grammar of the Aramaic scrolls, as well as their relationship to schematic astronomy in ancient Mesopotamia. Contributors examine the origin of the angelic tradition of the Watchers, the textual and literary relationship of the Aramaic scrolls to the Book of the Watchers, and the culpability of humanity in the spread of evil on earth according to the myth of the fallen angels"--
Includes index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Dead Sea Scrolls; Enoch -- (Biblical figure); Manuscripts, Aramaic -- West Bank -- Qumran Site; Konferenzschrift -- 2020 -- online; Aufsatzsammlung